2018
DOI: 10.1002/jsde.12048
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Cationic Gemini Asphalt Emulsifier

Abstract: A cationic Gemini surfactant with a benzene ring (abbreviated as C14‐CGB) was synthesized in 2 steps with aniline, epichlorohydrin, and N,N‐dimethyltetradecylamine as starting materials. This product was characterized using mass spectroscopy and nuclear magnetic resonance (1H NMR). The critical micelle concentration (CMC) and surface tension (γcmc) of C14‐CGB were measured from 298 to 313 K and thermodynamic parameters of micellization were calculated. The results showed that the CMC and γcmc were 1.269 × 10−3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[30] However, the droplet size of the emulsion stabilized by MCTS ranged from 0.90 μm to 2.30 μm, the mean size is about 1.79 μm, and the PDI of the sample is 0.206, which indicated that the asphalt emulsion is more uniform compared with the asphalt emulsion prepared by other emulsifiers. [1,31] It also can be seen from Figure 5(a); the prepared emulsion presented uniform and fine brown texture, which was usually a sign that asphalt was well emulsified. Therefore, the emulsifier exhibited excellent emulsifying ability in the manufacture of asphalt emulsion based on the above data.…”
Section: Application Of Mcts In Asphaltmentioning
confidence: 77%
See 4 more Smart Citations
“…[30] However, the droplet size of the emulsion stabilized by MCTS ranged from 0.90 μm to 2.30 μm, the mean size is about 1.79 μm, and the PDI of the sample is 0.206, which indicated that the asphalt emulsion is more uniform compared with the asphalt emulsion prepared by other emulsifiers. [1,31] It also can be seen from Figure 5(a); the prepared emulsion presented uniform and fine brown texture, which was usually a sign that asphalt was well emulsified. Therefore, the emulsifier exhibited excellent emulsifying ability in the manufacture of asphalt emulsion based on the above data.…”
Section: Application Of Mcts In Asphaltmentioning
confidence: 77%
“…The storage stability of asphalt emulsion under ambient temperature after 1 day and 5 days were 0.24% and 2.76%, respectively, which was more stable compared to that of the emulsion by using Gemini surfactant . The stability of the emulsion is relative to the droplet size and its distribution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations